The Rise and Decline of Nations : Economic Growth, Stagflation, and Social Rigidities - Olson, Mancur (London Yale University Press, 2022)
A compelling theory on the rationale for the changing fortunes of nations
Include Index
Keywords: Economic development -- Economics -- Unemployment--Effect of inflation on